Animation of planning algorithms - Sun, Fan (2014)
Planning is the process of creating a sequence of steps/actions that will satisfy a goal of a problem. The partial order planning (POP) algorithm is one of Artificial Intelligence approach for problem planning. By learning G52PAS module, I find that it is difficult for students to understand this planning algorithm by just reading its pseudo code and doing some exercise in writing. Students cannot know how each actual step works clearly and might miss some steps because of their confusion. Although there are some animations for planning algorithms, no animation for the POP algorithm exists so far. Therefore, the aim of this project is to create an animation of Partial Order Planning which can display the process of the method dynamically. It is an interactive and expressive web application, writing by java and web programming, which animates the pop algorithm in solving various examples of problems for a fixed domain (e.g. The Blocks World). As an educational tool, it assists G52PAS students in obtaining an in-depth understanding of the partial order planning (POP) algorithm and its process. In this web application, the animation of the partial order planning algorithm is displayed in detail. The students can control the animation easily, such as controlling the speed of the animation and pausing the animation at any time. Each step of planning process in the Blocks World is explained clearly. Overall, this web application is more comprehensive than any existing animation.